Defining the Current Practice of Facilities Management Service Delivery in Klang Valley (KV) Shopping Centres - Mohd.Nur, Norafiziah; Musa, Zairul Nisham (Journal of Surveying, Construction and Property, 2017)
The study on facilities management (FM) service delivery, especially in shopping centres, covered Klang Valley area rarely found in previous literature. This paper is imperative in helping the facilities management industry to understand more about the perceptions of the shopping centres, industry and their requirements towards FM services in shopping centres in order to deliver quality, innovative, cost effective and best in value services. Questionnaire survey is used as the tool to collect the primer data. Data collected includes the types of FM services, current FM service provision, the criticality of FM service towards overall business operation. The sample size for this survey is 108 shopping centre, which was chosen randomly among all shopping centres within the Klang Valley areas. The findings from this research showed that there are 11 types of FM services currently being practiced in Klang Valley (KV) shopping centres. The most critical FM services are determined according to each size of the shopping centre. It is confirmed that the shopping centres in Klang Valley deliver the FM services using both provisions that include in-house and outsourcing. However, the majority of Klang Valley shopping centre management is still favored in-house FM service delivery as compared to outsourcing.